Degradation of poly (2-ethyl-2-oxazoline) prepared at lower temperature: a study of kinetics using thermal analysis and advanced predictive modeling - Abdulrahman Alarabi; Imtiaz Ali (Discover Chemical Engineering)
Abstract The thermal degradation kinetics of poly(2-ethyl-2-oxazoline) (PEOX) prepared under different pH conditions were studied. Kinetic assessment was conducted by analyzing the thermal degradation of PEOX. The kinetic parameters were estimated using model-free methods; including Friedman, OFW, KAS and Starink methods and model-fitting method; Combined kinetics (Ck). The investigation revealed that the activation energy of PEOX degradation exhibited variability when prepared under different pH conditions. During the process of conversion, the activation energy for PEOX thermal degradation showed an increase when synthesized under neutral conditions, while it remained consistent when synthesized under alkaline conditions. The synthesis of PEOX in an acidic medium led to a compromised thermal stability, as indicated by a gradual reduction in activation energy during its thermal degradation. By employing artificial neural network (ANN) and advanced classification regression tree (C&RT), the prediction of activation energy's evolution was conducted, taking into account pH, conversion, heating rate, and temperature. The predictive performance of the advanced C&RT model surpassed that of ANN in determining the activation energy of PEOX degradation at different pH levels for different heating rates.